2008
DOI: 10.1111/j.1369-1600.2008.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Protracted ‘anti‐addictive’ effects of adolescent phenylpropanolamine exposure in C57BL/6J mice

Abstract: Exposure to the once highly prevalent over-the-counter (OTC) sympathomimetic phenylpropanolamine (PPA; +/--norephedrine) during pre-adolescence alters the developmental trajectory of catecholamine and amino acid neurotransmitter systems in the nucleus accumbens (NAC) that culminate in a 'pro-addictive' phenotype in adulthood. Thus, the present study sought to extend these earlier data by examining the long-term consequences of repeated PPA treatment during adolescence upon the behavioral and neurochemical resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Glutamate levels were sampled from the NAC shell in the present study, as we have observed previously a positive relation between the magnitude of cocaine CPP in mice and cocaine-elicited increases in extracellular glutamate within this subregion (see Szumlinski et al, 2007; Penzner et al, 2008). The NAC shell receives glutamatergic projections from both the ventral prelimbic (vPL) and the infralimbic (IL) subdivisions of the mPFC (Heidbreder and Groenewegen, 2003), which is in line with our observation that Homer2b cDNA over-expression primarily within the vPL and the vPL-IL interface (Figure 2A) impacted extracellular glutamate within the NAC shell (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate levels were sampled from the NAC shell in the present study, as we have observed previously a positive relation between the magnitude of cocaine CPP in mice and cocaine-elicited increases in extracellular glutamate within this subregion (see Szumlinski et al, 2007; Penzner et al, 2008). The NAC shell receives glutamatergic projections from both the ventral prelimbic (vPL) and the infralimbic (IL) subdivisions of the mPFC (Heidbreder and Groenewegen, 2003), which is in line with our observation that Homer2b cDNA over-expression primarily within the vPL and the vPL-IL interface (Figure 2A) impacted extracellular glutamate within the NAC shell (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the relevance of our reported cocaine-induced increase in mPFC Homer2 vs. Homer1 expression (Ary and Szumlinski, 2007) for cocaine-induced changes in behavior, the effects of manipulating mPFC Homer2b levels upon cocaine reward and locomotor sensitization were assessed using a unbiased conditioned place-preference (CPP) procedure (e.g., Szumlinski et al, 2007; Penzner et al, 2008). The CPP paradigm was selected for the study of AAV interactions with cocaine for its procedural simplicity, the ability to index both the positive and negative motivational valence of cocaine-associated cues and the ability to index both cocaine reward and locomotor activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures for cocaine place-conditioning and assessment of locomotor activity were similar to those described previously (Penzner et al, 2008; Szumlinski et al, 2007). Briefly, all experiments were conducted in a Plexiglas apparatus (46 cm long × 24 cm high × 22 cm wide) with a sound-attenuating lid and a removable center divider separating 2 compartments of equal size.…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus and procedures for heroin place-conditioning were similar to those employed in our previous studies of drug-conditioned reward in mice (e.g., Penzner et al, 2008) and proceeded in the following four sequential phases: habituation, preconditioning test (Pre-Test), conditioning, postconditioning test (Post-test). All sessions were 15 min in duration and animals received no injections during the habituation, Pre-Test, or Post-Test sessions when they had free-access to both compartments of the apparatus.…”
Section: Methodsmentioning
confidence: 99%